2018
DOI: 10.3390/genes9030161
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing in the Hippo Pathway—Implications for Disease and Potential Therapeutic Targets

Abstract: Alternative splicing is a well-studied gene regulatory mechanism that produces biological diversity by allowing the production of multiple protein isoforms from a single gene. An involvement of alternative splicing in the key biological signalling Hippo pathway is emerging and offers new therapeutic avenues. This review discusses examples of alternative splicing in the Hippo pathway, how deregulation of these processes may contribute to disease and whether these processes offer new potential therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 140 publications
0
12
0
Order By: Relevance
“…Through the in-depth genomic and functional studies, AS abnormalities and generated specific subtypes have been identified as driving factors of tumors (Oltean and Bates, 2014;Todaro et al, 2014). Furthermore, AS events involving oncogenic processes have been reported, including angiogenesis, metastasis, proliferation, apoptosis, and invasion (David and Manley, 2010;Porazinski and Ladomery, 2018). Notably, AS events are mainly regulated by splicing factors (SFs), whose mutations (Salton et al, 2015) or changes in expression may cause AS abnormalities (Shilo et al, 2014;Sveen et al, 2016) and activation of oncogenes and tumorigenic pathways (Shilo et al, 2014;Koh et al, 2015;Salton et al, 2015;Dvinge et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Through the in-depth genomic and functional studies, AS abnormalities and generated specific subtypes have been identified as driving factors of tumors (Oltean and Bates, 2014;Todaro et al, 2014). Furthermore, AS events involving oncogenic processes have been reported, including angiogenesis, metastasis, proliferation, apoptosis, and invasion (David and Manley, 2010;Porazinski and Ladomery, 2018). Notably, AS events are mainly regulated by splicing factors (SFs), whose mutations (Salton et al, 2015) or changes in expression may cause AS abnormalities (Shilo et al, 2014;Sveen et al, 2016) and activation of oncogenes and tumorigenic pathways (Shilo et al, 2014;Koh et al, 2015;Salton et al, 2015;Dvinge et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being decisive in the regulation of cell differentiation and cell-type-specific functions, abnormal variations in AS are also indispensable in multiple pathological processes, including cancers [ [7] , [8] , [9] ]. Accumulated evidence highlights the multifaceted AS events in several carcinogenesis hallmarks, including sustaining proliferative signaling, evading growth suppressors, angiogenesis, invasion, and metastasis [ 10 ]. More importantly, new trends in cancer research show that AS has emerging clinical potential in cancer therapy [ 5 , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant AS is involved in the development process of cancer [23][24][25]. TCGA RNA sequencing data and TCGA SpliceSeq data have enabled investigation of AS patterns in many different kinds of cancers, such as breast cancer (28), ovarian cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AS is not crucial for normal physiological processes such as hematopoiesis [19], brain development [20] and skeletal muscle function [21], but also for multiple pathological states, including tumorigenesis [22]. Aberrant AS is involved in many oncogenic processes, including uncontrolled cell proliferation, evading growth suppressors, invasion and metastasis, angiogenesis and immune escape [23][24][25]. More importantly, dysregulation of AS is a fundamental process in cancer and research shows that AS has emerging potential therapeutic targets and biomarkers in cancer therapy [16,22,26].…”
Section: Introductionmentioning
confidence: 99%